2019
DOI: 10.1002/joc.6260
|View full text |Cite
|
Sign up to set email alerts
|

Direct and indirect seasonal rainfall forecasts for East Africa using global dynamical models

Abstract: Regional‐scale seasonal climate outlooks are typically produced using forecast information either local to the region or from another area with teleconnections to the region. Dynamical global long‐range forecast (LRF) systems can provide both types of information, and these two approaches are compared in the context of seasonal rainfall forecasts for two adjoining areas in the Greater Horn of Africa region in tropical East Africa. The direct method utilizes the unprocessed LRF outputs for the region. For the “… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
10
0
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 13 publications
(12 citation statements)
references
References 30 publications
1
10
0
1
Order By: Relevance
“…From these results, we can conclude the skill from May from the hybrid approach exceeds or matches the average performance of direct model predictions initialized in August but is lower than that of best performing models and the statistical method. The relatively good performance of the hybrid models is consistent with Colman et al (2020) who found that combining statistical and dynamical prediction methods for East Africa could enhance skill.…”
Section: Discussionsupporting
confidence: 84%
See 1 more Smart Citation
“…From these results, we can conclude the skill from May from the hybrid approach exceeds or matches the average performance of direct model predictions initialized in August but is lower than that of best performing models and the statistical method. The relatively good performance of the hybrid models is consistent with Colman et al (2020) who found that combining statistical and dynamical prediction methods for East Africa could enhance skill.…”
Section: Discussionsupporting
confidence: 84%
“…The relatively good performance of the hybrid models is consistent with Colman et al . (2020) who found that combining statistical and dynamical prediction methods for East Africa could enhance skill.…”
Section: Discussionmentioning
confidence: 99%
“…Peramalan tidak langsung jarang dilakukan padahal dalam beberapa kasus dapat menghasilkan nilai ramalan dengan tingkat kesalahan yang kecil. Beberapa penelitian yang menggunakan konsep peramalan tidak langsung diantaranya adalah Petrorius & Botha (2010), Komara (2012), Shi et al (2011), Amendola & Candila (2017), Moosa & Vaz (2018), Colman et al (2020).…”
Section: Media Statistikaunclassified
“…Hybrid methods then combine dynamic and statistical methods (Slater et al ., 2022). Some hybrid methods generate indirect rainfall forecasts by extracting related variables (e.g., SST) from the GCMs and then statistically translate those values to target variables (e.g., Alfaro et al ., 2018; Strazzo et al ., 2019; Colman et al ., 2020). Indirect forecasts could perform well, as forecasts of large‐scale variability like SST over tropical domains are often a strength of the GCMs compared to their forecasts of more variable parameters like rainfall (Barnston et al ., 2012; 2019; Saha et al ., 2014).…”
Section: Introductionmentioning
confidence: 99%